Syphilitic gumma presenting as squamous cell carcinoma of Vulva: A case report - R.M. Nuss; A.J. Lazenby; H.C. Provost; T. Castellano (Elsevier, 2024)
Introduction: Tertiary syphilis, a late form of the disease with neurologic, cutaneous, and cardiovascular manifestations, is rarely seen in the United States in modern times. Also called the "great imitator," syphilis tends to mimic other disease processes, which can lead to a delay in proper diagnosis and treatment. Case: We present the case of a 59-year-old woman who presented for evaluation of possible squamous cell carcinoma of the vulva. After multiple inconclusive biopsies and extensive workup with multiple providers, she was instead found to have cutaneous and neurologic tertiary syphilis. A correct diagnosis was delayed in this patient due to a presentation not consistent with classical teachings and due to a lack of access to care. Conclusion: Syphilis has characteristic signs and symptoms, but in practice, it can have an indolent presentation that may differ from traditional presentations. To our knowledge, this is the first comprehensive case report of vulvar cutaneous syphilis masquerading as squamous cell carcinoma of the vulva. This case also provides additional evidence for the necessity of comprehensive gynecologic care and sexual history-taking in the post-menopausal populations and in rural communities.